Scoping Review: The Effectiveness Of Sanitation Interventions In Addressing Waterborne Diseases In Vulnerable Communities - Yusrina Nur Rahma; Dewi Purnamawati (International Journal of Health Engineering and Technology, 2026)
Waterborne diseases remain a serious public health concern in vulnerable communities, particularly in areas with inadequate sanitation. WHO reported approximately 505,000 diarrhea-related deaths annually due to unsafe drinking water. Indonesia's 2023 Health Survey showed diarrhea prevalence of 4.3% across all age groups. This scoping review aims to critically map and evaluate the effectiveness of various sanitation interventions in combating waterborne diseases in vulnerable communities based on current scientific evidence. The scoping review followed the Arksey and O'Malley (2005) framework, strengthened with JBI guidance, and reported using PRISMA-ScR guidelines. Searches were conducted through Google Scholar, PubMed, and Scopus (2020-2025). Sixteen articles were analyzed using descriptive thematic analysis. Multi-component sanitation interventions combining behavioral change with infrastructure provision demonstrated higher effectiveness than single interventions. Point-of-use water treatment reduced diarrhea risk by up to 50%, while handwashing with soap reduced risk by 30%. CLTS/STBM programs significantly improved latrine coverage and reduced diarrhea prevalence. Intervention effectiveness was moderated by seasonal variation, geographic context, and community participation levels. Multi-component approaches integrating behavioral change, infrastructure improvement, and institutional strengthening proved most effective. Significant research gaps exist regarding long-term sustainability, cost-effectiveness analysis, and climate change adaptation.